A single but prolonged and eventually fatal episode of capillary leak syndrome with a diagnosis of a small tumor mass B cell lymphoma - Schlier, Majorie; Rondeau-Lutz, Murielle; Weber, Jean-Christophe (Journal of Advances in Internal Medicine, 2014)
The capillary leak syndrome is a rare and serious condition. It is characterized by acute episodes of extravasation of liquids and proteins through the capillary wall to the interstitial space, with generalized edema, hemoconcentration, hypoproteinemia. Most often, capillary leak syndrome is idiopathic. Some cases are associated with neoplastic diseases. We describe a new case of capillary leak syndrome as a paraneoplastic syndrome of a large-B-cell lymphoma. This case is unusual because of the evolution of the capillary leak syndrome during a single but extended and fatal episode. The etiologic diagnosis in this case was particularly difficult to prove because of the small tumour mass. Our case report is thus the fourth reported case of capillary leak syndrome revealing a B-cell lymphoma with a small tumour mass. DOI: http://dx.doi.org/10.3126/jaim.v3i1.10702 Journal of Advances in Internal Medicine 2014;03(01):34-37